2009
DOI: 10.1111/j.1471-0307.2008.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high intensity pulsed electric fields on enzymes and vitamins in bovine raw milk

Abstract: Pulsed electric fields (PEF) were applied to fresh bovine raw milk using a laboratory-scale continuous PEF system to study the impact on selected native enzyme activities and on vitamin degradation. The activities of protease, lipase, alkaline phosphatase and lactoperoxidase following PEF treatment at electric field strengths ranging from 15 to 35 kV/cm for treatment times of 12.5 μs to 75 μs were examined. Reductions in enzyme activity, even under the most severe conditions employed, were quite modest, amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 31 publications
0
19
0
2
Order By: Relevance
“…Researchers investigated the consequences of PEF parameters (18.3, 22.6, and 27.1 kV/cm; 47–400 µs) on riboflavin and thiamine from milk, and reported no significant changes with processing (Bendicho et al, ). Likewise more data for milk were reported with a different set of parameters (15–35 kV/cm, 12.5–75 µs) that sowed similar results, since PEF did not alter contents of thiamin, riboflavin, and other vitamins (Riener et al, ). Thus far, research implied that PEF has minimal influence on concentration of B‐complex vitamins and it is likely that its adequacy for processing will increase with the need for higher processing temperatures during food manufacturing (e.g., needed for microorganisms that are more resilient).…”
Section: Nutritional Propertiesmentioning
confidence: 59%
See 1 more Smart Citation
“…Researchers investigated the consequences of PEF parameters (18.3, 22.6, and 27.1 kV/cm; 47–400 µs) on riboflavin and thiamine from milk, and reported no significant changes with processing (Bendicho et al, ). Likewise more data for milk were reported with a different set of parameters (15–35 kV/cm, 12.5–75 µs) that sowed similar results, since PEF did not alter contents of thiamin, riboflavin, and other vitamins (Riener et al, ). Thus far, research implied that PEF has minimal influence on concentration of B‐complex vitamins and it is likely that its adequacy for processing will increase with the need for higher processing temperatures during food manufacturing (e.g., needed for microorganisms that are more resilient).…”
Section: Nutritional Propertiesmentioning
confidence: 59%
“…Customer acceptance of beverages is directly dependent on sensory and nutritional quality attributes (Riener, Noci, Cronin, Morgan, & Lyng, ; Soliva‐Fortuny et al, ). Earliest findings for PEF referred to the evaluation of content of sugars, pH, acidity, and browning rate (Evrendilek et al, ; Yeom, Streaker, Zhang, & Min, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the results of Castro et al (2001) indicate a PEF based ALP inactivation that is directly related to the ALP concentration and the electric field intensity in terms of electric field strength and number of pulses. Riener et al (2009) reported a 29% inactivation of ALP in raw milk after PEF treatment at 35 kV/ cm and 75 ls in a continuous system but the authors did not find any inactivation of LPO.…”
Section: Calculated and Experimental Pef-only Inactivationmentioning
confidence: 91%
“…La aplicación de PEF ha sido ampliamente estudiada en una gran variedad de zumos, principalmente de naranja (Sitzmann, 1995; Zhang et al., 1997), manzana (Simpson et al, 1995;Vega-Mercado et al, 1997;Charles-Rodríguez et al, 2007;Noci et al, 2008), y tomate (OdriozolaSerrano et al, 2009), así como en zumos de arándanos, mandarina, limón y pomelo (Cserhalmi et al, 2006) y mezclas de naranja y zanahoria (Rivas et al, 2006). Los resultados obtenidos indican, en general, una mejora en la calidad del zumo con respecto al tratamiento térmico convencional (Min et al., 2007), ofreciendo productos con una aceptable vida útil, características sensoriales más parecidas al fresco, sin afectar aparentemente, o en menor medida que el tratamiento térmico, a las propiedades fisicoquímicas o atributos de calidad, principalmente color, pH, ºBrix, viscosidad y turbidez.…”
Section: Vida úTil Propiedades Físicas Y Sensorialesunclassified
“…Grahl y Märkl (1996) describieron que el tratamiento PEF reducía considerablemente el contenido en vitamina C de la leche, mientras que el contenido en vitamina A no se vio afectado. Riener et al (2008) tampoco observaron cambios en los niveles de vitaminas (tiamina, riboflavina, retinol, α-tocoferol) de leche tratada por PEF. Por otra parte, Introducción .…”
unclassified